3PLSPs in Pakistan: An Exploratory Study on MRO, Term of Service, Unique usiness Models, Fueling and Fee Charging Strategies, Adopted by MNCs and Domestic Firms - ZEESHAN NOOR SIDDIQUI; KAMRAN NOOR SIDDIQU (Journal of Business & Tourism, 2021)
An exploratory study that endeavors to bring out new dimensions related to 3PLPS through phenomenological approach. The study qualitatively highlights„MRO‟ (maintenance repair operation), and „term of service‟ as contributing propositions towards „fee charging strategies‟. During course of data collection and thematic analysis another proposition „fueling strategy‟ is also highlighted. Data is collected through semistructured interviews, conducted from four (4) 3PLSPs, Selected through „purposive sampling‟ with an expert of the domain. Set of recommendations include „policy recommendation‟ for the policy makers, and individual recommendations for all 3PLSPs working in Pakistan. Future research endeavors in the field of MRO, term of service, fueling, and fee charging strategies are also suggested. This study is a pioneering effort to explore and develop our understanding about these dimensions that directly or indirectly affect 3PLSPs.